Revictimization and Victim Satisfaction in Domestic Violence Cases Processed in the Quincy, Massachusetts, District Court, 1995-1997 - Hotaling, Gerald T. ([Verlag nicht ermittelbar], 2003)
This study sought to examine (1) the occurrence of revictimization, (2) the impact of case processing in Quincy District Court (QDC) on the disclosure of revictimization, and (3) victim satisfaction with various components of the criminal justice system. This study was undertaken as part of a secondary analysis of data originally collected for a National Institute of Justice (NIJ) sponsored evaluation of a "model" domestic violence program located in Quincy, Massachusetts (RESPONSE TO DOMESTIC VIOLENCE IN THE QUINCY, MASSACHUSETTS, DISTRICT COURT, 1995-1997 [ICPSR 3076]). Administrative records data were collected from the Quincy District Court's Department of Probation, two batterer treatment programs servicing offenders, and police incident reports, as well as survey data administered to victims. Included are criminal history data, records of civil restraining orders, probation department data on prosecutorial charges, case disposition and risk assessment information, data on offender treatment program participation, police incident reports, and self-report victim survey data. These data were collected with three primary goals: (1) to obtain the victim's point of view about what she wanted from the criminal justice system, and how the criminal justice system responded to the domestic violence incident in which she was involved, (2) to get details about the study incidents and the context of the victim-offender relationship that are not typically available in official statistics, and (3) to hear directly from victims about the defendant's reoffending behavior.